2017
DOI: 10.1080/23328940.2017.1288688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive heating on heat shock protein 70 and interleukin-6: A possible treatment tool for metabolic diseases?

Abstract: Increasing physical activity remains the most widely publicized way of improving health and wellbeing. However, in populations that benefit most from exercise (EX), adherence is often poor and alternatives to EX are important to bring about health improvements. Recent work suggests a role for passive heating (PH) and heat shock proteins (HSP) in improving cardio-metabolic health. The aim of this study was to investigate the expression of HSP70 and interleukin-6 in response to either EX or PH and the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 63 publications
6
40
2
1
Order By: Relevance
“…; Faulkner et al . ), which was also observed in the present study (on average, an ∼2‐fold increase). [IL‐6] was also increased following exposure to sera collected following the first hot water immersion session (Acute HT).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…; Faulkner et al . ), which was also observed in the present study (on average, an ∼2‐fold increase). [IL‐6] was also increased following exposure to sera collected following the first hot water immersion session (Acute HT).…”
Section: Discussionsupporting
confidence: 91%
“…For example, IL-6 is elevated acutely following exercise and is thought to mediate adaptation to exercise training (Pedersen & Fischer, 2007). Similarly, IL-6 has been shown to be elevated following acute hot water immersion (Leicht et al 2015;Faulkner et al 2017), which was also observed in the present study (on average, an ß2-fold increase). was also increased following exposure to sera collected following the first hot water immersion session (Acute HT).…”
Section: Basal Effects Of Heat Pretreatment and Serum Exposuresupporting
confidence: 85%
“…(7,19,20) The effects of other types of passive heat therapy such as Waon therapy, infrared-ray saunas, warm water immersion, and Turkish baths on inflammation and oxidative stress have been reported in several studies. (21)(22)(23)(24)(25) A number of studies have also suggested that exposure to Finnish sauna may be associated with alteration in concentrations of essential markers of inflammation and oxidative stress. (26)(27)(28)(29) However, these previous findings were however based on short-term effects of sauna exposure or cross-sectional associations.…”
Section: Introductionmentioning
confidence: 99%
“…In human whole-body passive heating models, such as hot water immersion of >60 min whereby core body temperature is increased, higher extracellular HSP70 concentration (Faulkner et al, 2017), and intracellular HSP70 changes (Oehler et al, 2001), have been reported. The beneficial response once again is not unanimous, with others reporting chronic change (following 2 weeks of repeated therapy) in intracellular HSP70 after 45-60 min of passive heat therapy (Hoekstra et al, 2018).…”
Section: Chronic Effects Of Body Warming On Heat Shock Proteinsmentioning
confidence: 99%
“…Several mechanistic pathways may underpin these adaptations, including improved cellular respiration , circulating factors (Brunt et al, 2019), and vascular shear stress (Tinken et al, 2009;Thomas et al, 2016). The upregulation of heat shock proteins (HSPs) as a result of acute and/or chronic (repeated) exposure to passive heating is also an adaptive outcome, which may provide a specific mechanistic pathway for improving health and function within the body (Faulkner et al, 2017;Brunt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%